THERMO GRAVIMETRY-DIFFERENTIAL SCANNING COLORIMETRY-MASS SPECTROSCOPY-A REVIEW - SRI, K. BHAVYA; SHAILAJA, G. SRI VANI (International Journal of Current Pharmaceutical Research, 2021)
Thermogravimetric analysis is an analytical technique used to determine a material's thermal stability and its fraction of volatile components by monitoring the weight change that occurs as a sample is heated at a constant rate. Differential scanning colorimetry analysis is used to measure melting temperature, the heat of fusion, latent heat of melting, reaction energy etc. Mass spectroscopy is a powerful analytical tool with many applications in pharmaceuticals and biomedical fields. The increase in sensitivity and resolution of the instrument as opened new dimensions in analysis of pharmaceuticals and complex metabolites of biological systems. Thermo gravimetry coupled with differential scanning colorimetry and Quadra pole mass spectrometry was applied to monitor the thermal stability and chemical properties of natural polymers isolated from chemically different soils. The TGA/DSC, when coupled with MS generic multiple ions from the sample under investigation, it then separates them according to a specific mass-to-charge ratio. The coupled instrument is used for simultaneous identification of organic compounds, used to evaluate the physical properties, degradation stability of powder coating.